Variants of the microsomal triglyceride transfer protein gene are associated with plasma cholesterol levels and body mass index. - Ledmyr, H; Karpe, F; Lundahl, B; McKinnon, M; Skoglund-Andersson, C; Ehrenborg, E (2002)
The microsomal triglyceride transfer protein (MTP) is required for the assembly and secretion of apolipoprotein B (apoB)-containing lipoproteins from liver and intestine. We set out to study the phenotypic modulation of all common genetic variants in the MTP gene. In addition, we aimed at characterizing the association between the various polymorphisms. A total of 564 healthy men were genotyped for the MTP -493 G/T, -400 A/T, and -164 T/C promoter polymorphisms, as well as the Q/H 95, I/T 128, Q/E 244, and H/Q 297 missense polymorphisms. The -493 G/T, -164 T/C, and I/T 128 polymorphisms showed to be in almost complete linkage disequilibrium. Subjects homozygous for the less common -493 T, -164 C, and T 128 alleles showed significantly lower plasma total and LDL cholesterol levels and plasma LDL apoB levels, and also significantly higher body mass index (BMI) and plasma insulin levels compared with carriers of the common alleles. The associations between plasma total cholesterol and MTP -493 genotype was verified in a cohort consisting of 1,117 disease-free control subjects of the West of Scotland Coronary Prevention Study (WOSCOPS). None of the other polymorphisms showed any significant change in either lipid and lipoprotein levels or anthropometric variables. In summary, two promoter polymorphisms and one missense polymorphism in the MTP gene alter plasma total and LDL cholesterol levels, plasma LDL apoB levels, BMI, and insulin levels. This may, in turn, have implications for genetic regulation of cardiovascular risk factors.